Arteriovenous Malformation of the Prostate Vasculature as a Cause of Torrential Bleeding during Transurethral Resection of the Prostate - Darshan Sitharthan; Athos Katelaris; Gordon O’Neill (Société Internationale d’Urologie Journal)
An 82-year-old male experienced severe bleeding during transurethral resection of the prostate (TURP) due to an undetected prostatic arteriovenous malformation (AVM). Initial management with a catheter was followed by successful transarterial embolisation. This case highlights the effectiveness of endovascular angioembolisation for unexpected prostatic AVMs.